Optimum Pre-Release Strategy for Dam in Perak as Improved Decision Making Support System - ISHAK, NURUL HIDAYAH (2019)
Flood is one of the most frequent natural disasters that happens almost every year in Malaysia, which is a major concern to the public and the government. To date, one of the most disastrous flood events occurred in Perak, a state in Peninsular Malaysia in 2014, which tremendously affected the local community and the environment.